Design, Challenges, and Implications of Quality Improvement Projects Using the Electronic Medical Record: Case Study. (September 2016) - Ebinger, Joseph E.; Porten, Brandon R.; Strauss, Craig E.; Garberich, Ross F.; Han, Christopher; Wahl, Sharon K.; Sun, Benjamin C.; Abdelhadi, Raed H.; Henry, Timothy D.
Abstract : Postoperative atrial fibrillation (POAF) is a frequent complication of cardiac surgery, which results in increased morbidity, mortality, length of stay, and hospital costs. We developed and followed a process map to implement a protocol to decrease POAF: (1) identify stakeholders and form a working committee, (2) formal literature and guideline review, (3) retrospective analysis of current institutional data, (4) data modeling to determine expected effects of change, (4) protocol development and implementation into the electronic medical record, and (5) ongoing review of data and protocol adjustment. Retrospective analysis demonstrated that POAF occurred in 29.8% of all cardiovascular surgery cases. Median length of stay was 2 days longer ( P <0.001), and median total variable costs 2495 higher ( P <0.001) in POAF patients. Modeling predicted that up to 60 cases of POAF and >200 000 annually could be saved. A clinically based electronic medical record tool was implemented into the electronic medical record to aid preoperative clinic providers in identifying patients eligible for prophylactic amiodarone. Initial results during the 9-month period after implementation demonstrated a reduction in POAF in patients using the protocol, compared with those who qualified but did not receive amiodarone and those not evaluated (11.1% versus 38.7% and 38.8%; P =0.022); however, only 17.3% of patients used the protocol. A standardized methodological approach to quality improvement and electronic medical record integration has potential to significantly decrease the incidence of POAF, length of stay, and total variable cost in patients undergoing elective coronary artery bypass graft and valve surgeries. This framework for quality improvement interventions may be adapted to similar clinical problems beyond POAF. Abstract : Supplemental Digital Content is available in the text.